A GIS-based procedure for preliminary mapping of pluvial flood risk at metropolitan scale. (September 2018) - Di Salvo, Cristina; Pennica, Francesco; Ciotoli, Giancarlo; Cavinato, Gian Paolo
Abstract: A GIS-based procedure for mapping pluvial flood risk in urban areas is proposed; risk is expressed through an index calculated as the sum of susceptibility and potential impact, combined in a matrix. The susceptibility is defined as the probability of a flooding to occur, because of the ground morphology and the spatial probability density of historical floodings. The potential impact was evaluated by considering the consequences of damages on human health, environment, cultural heritages and economic activities, and accounts for the potential cost of damage. Both the susceptibility and the potential impact are calculated by elaborations of base-data in GIS environment. Despite many limitations, the methodology furnishes a tool for a preliminary screening of areas potentially subjected to pluvial flood, useful for a municipal scale mapping. It permits comparative analysis for detecting areas higher at risk, helping prioritizing the emergency management and the planning of mitigation actions. Highlights: A simplified procedure for urban scale mapping of pluvial flood risk is proposed. A chain of GIS tools was used to process data and build the map. Risk is expressed as a matrix accounting for the sum of susceptibility and potential impact. Results were evaluated by comparing the calculated and observed damage costs.